Understanding Esports from the perspective of team dynamics - Tang, W. (The Sport Journal, 2018)
This paper provides an overview of the esports industry and outlines recent development in esports research, with a focus on studies concerning impacts of team dynamics on performance. The characteristics of successful esports teams are identified through discussion on the variety of team resources and composition, the conceptualization of team cohesion in different dimensions, and the functions of communication and social support within a high performing team. It is also understood that participation in esports not only requires teamwork and communication skills, but can also serve as an opportunity for players to develop a variety of life and social skills.